Predicting Intrauterine Growth Restriction in Hypertensive Pregnancy: Cerebroplacental Ratio and Umbilical Artery Waveform - Sahibzada, Samiya Iqbal; Iffat Naheed (Journal of University College of Medicine and Dentistry, 2024)
Objective: To evaluate the diagnostic accuracy of the cerebroplacental ratio compared to the umbilical artery waveform in predicting adverse fetal outcomes, specifically intrauterine growth restriction (IUGR), in hypertensive pregnancies. Methodology: This descriptive cross-sectional study of six months’ duration from August 2018 to February 2019 was carried out at the Department of Obstetrics & Gynecology, Lady Aitchison Hospital, Lahore on 160 females, who underwent ultrasonography by experienced radiologists. Cerebroplacental ratio and umbilical artery waveform was noted in form of resistive index (RI). Patients were categorized as positive or negative for respective methods. Females then underwent clinical evaluation for IUGR by experienced gynaecologists, and all the data was collected through proforma, entered and analyzed through SPSS 21. Sensitivity, specificity, positive predictive value (PPV),negative predictive value (NPV) and diagnostic accuracy of cerebroplacental ratio and umbilical artery waveform was measured. Results: The patients had mean age of 29.16 ± 6.92 years. The mean gestational age at enrollment was 35.58 ± 1.08 weeks. At recruitment, the mean systolic blood pressure of females was 168.97 ± 13.71 mmHg and diastolic blood pressure was 108.32 ± 8.56 mmHg. There were 142 (68.75%) patients with pregnancy induced hypertension while 18 (11.25%) had eclampsia. The mean BMI of patient was 24.14 ± 3.39kg/m2. The specificity, sensitivity, NPV, PPV and diagnostic accuracy of cerebroplacental ratio were 95.1%, 96.97%, 95.1%, 96.97% and 96.25% respectively whereas of umbilical artery waveform were 49.2%, 71.7%, 51.7%, 96.6% and 63.1%. Conclusion: The cerebroplacental ratio was more accurate than umbilical artery waveform for prediction of IUGR in hypertensive pregnancy.